Working with coaches and their teams in youth and collegiate sport in the USA: An interview with Dr Andy Gillham - Commentary - Magnusen, M. (International Journal of Sports Science & Coaching, 2018)
Although my commentary brings attention to the importance of leadership, culture, and the leadership-culture interaction, what I have provided only scratches the surface of these topics. These are complex areas that warrant serious consideration. With concerted study and reflection, consultants should be better able to recognize consulting opportunities to avoid (e.g. a weak team leader who lacks a strong desire to change a team`s culture) and consulting opportunities to pursue (e.g. a strong team leader who is willing to learn and who is fully supportive of culture change). They also should be better prepared to educate and train sport industry professionals in the ways of leadership and creating positive organizational cultures, such as Dr. Gillham was able to do with both figure skating clubs.